Zooarchaeological Evidence from Medieval Ojców Castle, Lesser Poland - Joanna Religa-Sobczyk; Krzysztof Wertz; Lembi Lõugas; Michał Wojenka; Anna Lemanik; Piotr Wojtal (Heritage, 2022)
Archaeological research at Ojców castle has yielded important information about life in that medieval castle. The results of zooarchaeological analyses presented in this paper complement the archaeological research, adding to our knowledge of the diet of the castle inhabitants from the time of establishment of the castle until the final residents. Zooarchaeological research is also complemented by data from older settlement phases on the castle hill, directly related to the Lusatian culture in the early Iron Age. The great variability of remains from mammals, birds, and fish and the taphonomic features of bones found in the different chronological strata of the castle’s courtyard reflect the diverse economic activities that took place in particular times and spaces.